Effects of inhaled hypertonic (7%) saline on lung function test in preschool children with cystic fibrosis: results of a crossover, randomized clinical trial - Raffaella Nenna; Fabio Midulla; Caterina Lambiase; Giovanna De Castro; Anna Maria Zicari; Luciana Indinnimeo; Giuseppe Cimino; Patrizia Troiani; Serena Quattrucci; Giancarlo Tancredi (BMC, 2017)
Abstract Background This crossover, randomized, double-blind study (conducted over a 32-week period) was performed to determine, in clinically stable Cystic fibrosis (CF) preschool children: the effects of 7% inhaled hypertonic saline on spirometry and interrupter resistance technique (Rint), and the possible side effects. Methods Twelve CF children (6M, mean age ± SD: 5.7 ± 0.8 yrs) were enrolled and randomly assigned to receive hypertonic saline (HS-4 ml 7% sodium chloride), or normal saline (NS-0.9% sodium chloride) twice a day. After a 16 weeks period, therapy was exchanged to allow all the patients enrolled in the study to carry out both treatments. Monitoring visits, spirometry (COSMED Quark PFT4 ergo) and Rint were scheduled at 0,4,16,20,32 weeks. At T0, spirometric measurements and Rint were performed immediately before and 30 min after the inhalation therapy. Salbutamol (400 mcg) was administered before the drug at each visit. Results After a 16-weeks treatment with HS an improvement of FVC (p = 0.02) and a favorable trend of FEV1 were registered. A worsening of FEV1 (p < 0.0001) and of FEF25-75 (p = 0.019) were found in NS group. No differences were found in expiratory and inspiratory Rint in both groups. No serious adverse events occurred. Conclusions Seven percent hypertonic saline therapy proved to be a useful and safe treatment in young CF children with clinically stable conditions. Trial registration ISRCTN12345678 .